Inefficient markets for energy efficiency: Empirical evidence from the German rental housing market - Lisa Taruttis; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2022)
Improving the energy efficiency of residential buildings is of paramount importance to reduce CO2 emissions and hence to achieve a climate-neutral building stock - the objective of the German government for 2045. Thereby, a focus on the existing building stock is needed, as regulations for new buildings are already quite tight in terms of energy efficiency, and a large proportion of the dwelling stock of 2045 already exists today. For the important segment of rental housing, split incentives are often invoked as an impediment for energy-related investments. Yet this implicitly takes the tenant-landlord relationship as given. On the market where prospective renters meet the dwelling offers, competitive forces and rational behavior on both sides would imply that the monthly net rent should reflect (with opposite sign) differences in expected monthly heating costs - other things being equal. We test this hypothesis by specifying a hedonic price model that reflects this gross-cost-of-renting perspective and applying it on a detailed dataset including dwelling and neighborhood characteristics. As a case study, we use data for the German state of North Rhine-Westphalia, which implies that variations in regulatory and meteorological conditions are small, while large socioeconomic differences across subregions exist (e.g., in terms of purchasing power or unemployment rates). Drawing on 844,229 observations from 2014 to 2020 on a small spatial scale, we find a premium for more efficient apartments; however, it is rather small. The expected energy cost savings exceed the premium by approximately a factor of six. Rather, we find large discounts if apartments use heating technologies that are known to be inefficient. The paper explores various explanations for these outcomes, considering both landlord and renter behavior as well as institutional settings.
Keywords: C21; Q40; R21; R31; 330; Energy efficiency; residential buildings; hedonic analysis; rental market